Autistic Spectrum Disorders – Explanatory Theories, Diagnostic Symptomatology and Prevalence. Case Studies: Array - Țăranu, Georgela (New Trends in Psychology, 2020)
The tremendous incidence of autism worldwide, but also in Romania, raised questions concerning the etiology, early diagnosis and effective therapeutic intervention. Due to the dramatic deteriorations induced by autism, it is considered a polyhandicap, in most cases of maximum severity. The ASD person is assisted for life, the quality and complexity of this support depending on conjectural social politics. Our range of support services provided (medical, rehabilitation, social) is not adapted to the special needs of the autistic person and their family. Consequently, academic and social integration of children/people with ASD is difficult and most often doomed to failure.